Neuropeptide cyclo-L-prolylglycine counteracts scopolamine-induced long-term memory impairment in rats in the novel object recognition test - O. N. Vorontsova; A. G. Alyaeva; K. N. Koliasnikova; E. A. Valdman; P. Yu. Povarnina (Фармакокинетика и Фармакодинамика)
Background. Cyclo-L-prolylglycine (CPG) was designed and synthesized at the V.V. Zakusov as a topological analogue of the classical nootrop piracetam and was further identiﬁed as an endogenous compound. Previously, the nootropic eﬀect of CPG was revealed in a model of retrograde amnesia in rats induced by electroconvulsive shock in the passive avoidance test (PAT).Objective. The aim of the present study was to investigate the nootropic eﬀect of CPG under more physiological conditions in the absence of strong stressors.Methods. Amnesia in rats was modeled by intraperitoneal (ip) administration of scopolamine at a dose of 2 mg/kg. CPG was administered ip at doses of 0.1 and 1.0 mg/kg 15 minutes after scopolamine. Short- and long-term memory were recorded in the novel object recognition test.Results. It was found that scopolamine disrupted only the long-term memory of rats. CPG at a dose of 0.1 mg/ kg almost completely counteracted this impairment. CPG by itself had no eﬀect on memory at both doses studied.Conclusion. Thus, CPG exhibits nootropic activity not only in the aversive conditions of the PAT and electroconvulsive shock-induced amnesia, but also in the neutral situation in the novel object recognition test, when the amnesia was caused by the administration of scopolamine.